Effect of substrate placement in schott vial to hematite properties - Wan Rosmaria Wan Ahmad; M. H. Mamat; A. S. Zoolfakar; Z. Khusaimi; A. S. Ismail; T. N. T. Yaakub; M. Rusop (Bulletin of Electrical Engineering and Informatics, 2019)
In the present study, hematite (α-Fe2O3) nanostructures were deposited on fluorine doped tin oxide (FTO) coated glass substrate using sonicated immersion synthesis method. The effect of FTO glass substrate placement in Schott vial during immersion process was studied on the growth of the hematite nanostructure and its properties. XRD pattern has revealed seven diffraction peaks of α-Fe2O3 for both hematite nanostructures samples attributed to polycrystalline with rhombohedral lattice structure. The surface morphologies from FESEM have shown that the hematite nanostructures were grown uniformly in both samples with FTO conductive layer facing up and down. Hematite sample with FTO facing down exhibits a smaller size of nanorod, 26.7 nm average diameter, compared to the hematite sample that FTO face up with 53.8nm average diameter. Optical properties revealed higher transmittance in the sample with FTO facing down, probably due to smaller size of nanostructure. The optical band gap energy plotted and extrapolated at 2.50eV and 2.55eV for FTO face up and FTO face down hematite samples respectively, presenting the sample with FTO face up has a lower optical bandgap energy.